Nalar Fidyah (Telaah Maqasid Al-Syariah Al-Iqtishadiyah) - Jefry Tarantang; Ahmad Dakhoir; Ahmad Balya Nasim Ahmad (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2021)
This research is a study of sharia reasoning regarding fidyah or relief from not carrying out Ramadan fasting in the study of maqashid al-syariah al-iqtishadiyah, by knowing the objectives, secrets and virtues, as well as their context in the development and economic development of the people. This research is library research with a multi-approach study of the concept of fidyah according to Islam, then looks at the implementation of fasting fidyah through maqashid al-sharia and in an economic context. This research uses a conceptual, historical, and contextual approach. The results of this study Allah wants ease of worship, especially in fasting by not forcing servants to fast for the elderly, such as the elderly or the elderly, pregnant and nursing mothers, people who experience illness with very little hope of recovery, and people who work hard. The obligation of fidyah be paid by feeding the poor and needy in a dose of one mudd or equal to 15 tahil or 567 grams or it can also be converted into staple food. Fidyah payments can be made at any time, if it is delayed then the payment will be doubled. According to the maqashid sharia, fidyah is a form of benefit and goodness given by God to his servants with regard to three elements of care, namely religion, soul and wealth. The release of wealth to elderly Muslims, fidyah also gave birth to an indication as an instrument and potential as well as economic development for the people, especially the poor. the implementation of fidyah has value, wisdom, and benefit to the giver and recipient of fidyah